Synergistic Effect of BaCl2 on Corrosion Inhibition of Copper by Mentha Spicata Oil in 1M Nitric Acid: Gravimetric and Raman Spectroscopy Studies - Belarbi, Nadia; Dergal, Fayçal; Chikhi, Ilyas; Lerari, Djahida; Dahmani, Benamar; Choukchou-Braham, Noureddine; Bachari, Khaldoun (Видавництво Львівської політехніки, 2023)
За допомогою методів втрати ваги та ман-спектроскопії досліджено вплив суміші олії Mentha Spicata та суміші BaCl2 й олії Mentha Spicata на корозію міді в 1M HNO3. Дослідження показало, що олія Mentha Spicata ефективніше інгібує мідь у присутності BaCl2 порівняні з самою олією. Ефективність інгібування збільшувалась із підвищенням концентрації добавок. З використанням самої лише олії Mentha Spicata dslpyfxtyj найвищу ефективність інгібування 56,12 %. Підвищену ефективність інгібування 75,13 % спостерігали для суміші олії Mentha Spicata і BaCl2 за 298 K в 1M HNO3; цей ефект пояснюється синергізмом між олією Mentha Spicata і BaCl2. Ефективність інгібування знижувалася з підвищенням температури від 298 до 328 K. Адсорбція молекул інгібітора на поверхні металу відповідала ізотермі Фрумкіна та Ленгмюра. Термодинамічні параметри, такі як ентальпія ∆H, вільна енергія адсорбції ∆G та ентропія адсорбції, були отримані з експериментальних температур у діапазоні 298–328 K. Для дослідження поверхневих шарів використовували Раман-спектроскопію та мапінг.

The effect of Mentha Spicata oil and the mixture of BaCl2 and Mentha Spicata oil on corrosion of copper in 1M HNO3 have been investigated using weight loss methods and Raman spectroscopy. The study revealed that copper is more efficiently inhibited by Mentha Spicata oil in the presence of BaCl2 than pure oil. The inhibition efficiencies increased with increased concentration of the additives. The highest inhibition efficiency of 56.12 % was observed with single Mentha Spicata oil. An improved inhibition efficiency of 75.13 % was observed with the mixture of Mentha Spicata oil and BaCl2 at 298 K in 1M HNO3, an effect attributed to synergism between Mentha Spicata oil and BaCl2. Inhibition efficiency decreased with increase in temperature from 298-328 K. The adsorption of inhibitor molecules on metal surface followed Frumkin and Langmuir isotherm. Thermodynamic parameters such as enthalpy ∆H, free energy of adsorption ∆G and entropy of adsorption are obtained from experimental temperatures ranging from 298-328 K. Raman Spectroscopy and mapping were used to characterize the surface layers.
Синергічний ефект BaCl2 на інгібування олією Mentha Spicata корозії міді в 1M нітратній кислоті: гравіметричне та раман-спектроскопічне дослідження
Keywords: корозія; мідь; олія Mentha Spicata; інгібітори; кисле середовище; синергізм; corrosion; copper; Mentha Spicata oil; inhibitors; acid medium; synergism